The Effect of Rotational Speed on Friction Stir Welding (FSW) Quality of Dissimilar Aluminum Alloy Series AA 1100 and AA 5052 - Tarkono Tarkono; Frengki Tenando; Nafrizal Nafrizal; Irza Sukmana (Jurnal POLIMESIN, 2023)
Aluminum and its alloy have been widely used in various fields of industries. Aluminum has superior properties in terms of corrosion and has an excellent tensile strength compared to other lightweight metals. Aluminum AA 1100 series is an alloy such as copper, iron, chromium, manganese, and zinc, and the minimum aluminum content is 99.0%. Moreover, Aluminum AA 5052 series is an alloy of aluminum with magnesium (Mg). Welding is the process of joining two or more base metals that are joined at the contact surface with or without additives or fillers. Friction Stir Welding (FSW) is an example of solid-state welding or non-fusion welding. FSW uses friction energy for the welding process, which generates from the indenter's twists to material surface and pressing force. Welding parameters and indenter shape change the spiral form with an indenter rotation of 1750 rpm, 2230 rpm, 3500 rpm, and a translation speed of 22 mm/minute. The tests are tensile testing, hardness testing, and microstructure testing. This study found that indenter rotation and welding speed significantly affect the mechanical properties of aluminum series 1100 and 5052, which have been welded. The higher the rotation of the indenter, the higher the hardness value, the increase in hardness reaches 10.2%. However, the higher the rotation of the indenter causes a decrease in tensile strength, with a decrease of 18.6%.